Aestheticizing language: metapragmatic distance and unequal Englishes in Hong Kong. Issue 2 (4th May 2019) - Lee, Jerry Won; Jenks, Christopher Joseph
Abstract: While scholars in World Englishes have long acknowledged the inherent equality of varieties of Englishes spoken within and across different nations, unequal relations across Englishes persist through various means. One such way, as discussed in this article, is through the aestheticization of language, which we define as a process in which individuals evaluate a language resource or usage as aesthetically appealing on the basis of its stylistic, grammatical, or phonological 'appearance.' This study, based on classroom ethnography in Hong Kong, demonstrates that language aestheticization is an ideological commitment that sustains a speaker's metapragmatic distance from English. Our analysis shows how aesthetic evaluations of language represent, and can exacerbate, social and linguistic inequalities. These findings contribute to current understandings of World Englishes in Asian contexts, in that metapragmatic distance is reflective of a complex interplay of ideology and access to dominant language resources.